Transformation of infusion system to automatically complete infusion tasks - Yao, Mingyu (Transactions on Computer Science and Intelligent Systems Research, 2024)
In the realm of medical technology advancements, there has been a significant enhancement in methodologies for investigating patient ailments and devising therapeutic interventions, surmounting myriad complex challenges in the process. Concurrently, the healthcare sector has adopted a diverse array of tools to accommodate various treatment modalities. Among these, the infusion device, a staple in clinical settings, is ubiquitously employed yet is considered to be archaic in its operational methodology. Predominantly utilized within hospital environments, the traditional infusion paradigm is notably labor-intensive, necessitating constant supervision to mitigate the risk of errors, a responsibility often delegated to patients or their guardians. This scholarly discourse aims to delineate the extant landscape and historical context of infusion device technology. It will methodically review and analyze existing literature on advancements in automation within the domain of infusion therapy, with the intention of synthesizing a comprehensive solution that epitomizes the zenith of current research findings. By comparing and contrasting various scholarly contributions on the subject, the paper endeavors to construct a cohesive overview of the advancements in automated infusion systems, thereby contributing to the ongoing discourse and potentially influencing future innovations in medical device technology.